2009
DOI: 10.1002/art.24366
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of relapsing polychondritis with rituximab: A retrospective study of nine patients

Abstract: Objective. Rituximab, a chimeric monoclonal antibody directed against the CD20 antigen expressed by B cells, is now considered an effective second-line therapy in various systemic diseases. We describe here the effects of rituximab in patients with relapsing polychondritis. Methods. This was a retrospective study of 9 patients with relapsing polychondritis who received different regimens of rituximab in addition to their ongoing therapies. Clinical, laboratory, physiologic, and radiologic indicators were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 24 publications
3
27
0
5
Order By: Relevance
“…Leroux et al [53] described nine patients with refractory disease, all of whom had received prior treatment with corticosteroids and a variety of immunosuppressive agents. Analysis at 6 and 12 months after initiation of rituximab revealed that no patient achieved complete remission, while some were stable and others deteriorated.…”
Section: Treatmentmentioning
confidence: 99%
“…Leroux et al [53] described nine patients with refractory disease, all of whom had received prior treatment with corticosteroids and a variety of immunosuppressive agents. Analysis at 6 and 12 months after initiation of rituximab revealed that no patient achieved complete remission, while some were stable and others deteriorated.…”
Section: Treatmentmentioning
confidence: 99%
“…There are isolated case reports of favourable response to rituximab in patients not responding to immunosuppressive therapy [78,79]. However, a retrospective study [80] of 9 patients treated with rituximab showed that at the end of 12 months of therapy, no patient was in partial or complete remission though depletion of B cells was demonstrated. Anti-TNF agents have been used successfully in patients with refractory RP.…”
Section: Managementmentioning
confidence: 99%
“…Die Hemmung von Interleukinen scheint sich insbesondere bei Organbeteiligung positiv auf die Krankheitsaktivität auszuwirken. Ferner werden aktuell mehr Fallberichte zu einem positiven Einsatz von Rituximab zur B-ZellDepletion veröffentlicht [22]. Darüber hinaus gibt es auch limitierte Erfahrungen mit Abatacept [23].…”
Section: Therapieunclassified